New aspects in the diagnosis and treatment of primary spontaneous pneumothorax - Dżeljilji, Agata; Rokicki, Wojciech; Rokicki, Marek; Karuś, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
This paper provides a recapitulation of the position of the British Thoracic Society and the American College of Chest Physicians based on a review of the literature concerning the current methods of diagnosing and treating primary spontaneous pneumothorax (PSP). The previously developed guidelines were re-evaluated in 2015 by a task force of the European Respiratory Society (ERS). They are intended to be used by surgeons as well as emergency and pulmonary ward physicians, and they apply largely to emergency procedures. In recent years, the effectiveness of minimally invasive methods (punctures, drainage) in combination with talc pleurodesis for the initial therapy of PSP has been recognized. The efficacy of thoracoscopy (VATS) for the treatment of this disease has been proven by the development of minimally invasive surgical techniques in thoracic surgery. This paper also discusses the efficacy of the surgical methods available.